SEJARAH DAN PERKEMBANGAN GEREJA HKBP RESSORT PEKANBARU (1952-2018) - Anwar Nababan, Siharta Leman; Ibrahim, Bedriati; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Pekanbaru Ressort HKBP Church is the first church in Pekanbaru that was established on January 21, 1952. The church was originally founded on Jl. Church (now Jl. Wolter Mangonsidi), then moved to another location on Jl. Hang Tuah No. 36 Pekanbaru, Sukmahilang Sub-District, Pekanbaru City District and was inaugurated on August 23, 1970. This study aims to (1) trace the history of the Pekanbaru HKBP Ressort Church, (2) to develop the Pekanbaru HKBP Ressort Church to be determined from 1952-2018, (3) to identify the contribution of the Pekanbaru Ressort HKBP Church to the surrounding community and (4) to identify the role of local government in the development of the Pekanbaru Ressort HKBP Church. determine. In this study, the authors use the historical method referred to by the historical method, an approach that draws attention to past research conducted by collecting sources from previous research used as a reference in the history of history. Data collected through observation, interviews, documentation and literature study. Data analysis uses a historical writing method that consists of several stages, namely heuristics, verification, interpretation and historiography. The research time starts from the submission of the title of the proposal to the completion of the author's dissertation. The results of this study are the history of the Pekanbaru HKBP Church Ressort, inseparable from the initial development that started long before Indonesia's independence, which began in the 1930s, which began with the first worship by only four people who later called the Christian communityKey Words: HKBP Church Pekanbaru Pekanbaru